Powerful high-orbit gyro-TWT - S. V. Kolosov; O. O. Shatilova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
This paper presents the results of a search for the optimal design of a high-orbit gyro-TWT, which would make it possible to reduce the magnetostatic field when operating at high frequencies close to the millimeter wavelength range, increase the gain and gain bandwidth, and increase the efficiency of the gyro-TWT. To search for the optimal configuration of the high-orbit gyro-TWT, the Gyro-K program was used, in which the equations for the excitation of an irregular waveguide by an electron beam are constructed on the basis of the coordinate transformation method of A.G. Sveshnikov, which is based on replacing the problem of exciting an irregular waveguide with the problem of exciting a regular waveguide with a unit radius. This method allows one to search for the solution of wave equations in the form of expansions in terms of the system of basis functions of a regular cylindrical waveguide. To solve Maxwell's equations, the Galerkin method was used, which is also called the orthogonalization method. The coefficients of the expansion of the field in terms of eigenbasic functions are determined in this method from the condition of the orthogonality of the residuals of the equations for the eigenbasis functions of a regular waveguide. The boundary conditions at the open ends of the waveguide are determined for each mode of the regular waveguide separately, which eliminates the incorrectness of setting the boundary conditions for the full field, as is the case when using the “picˮ technology. As a result, we obtain a system of ordinary differential equations for the expansion coefficients, which now depend only on the longitudinal coordinate. This approach makes it possible to transform the threedimensional problem of excitation of an irregular waveguide into a one-dimensional problem. Ohmic losses in the walls of the waveguide are taken into account on the basis of the Shchukin – Leontovich boundary conditions. For a self-consistent solution of the problem of excitation of an irregular waveguide by an electron beam, the iterative method of sequential lower relaxation was used. An optimized version of a high-orbit gyroTWT has been obtained, which has an electronic efficiency of 28 %, a wave efficiency of 23 %, a gain of 34 dB and a gain band of 11 % at an operating frequency of more than 30 GHz. This was achieved by introducing an additional conducting section of the waveguide into the absorbing part of the waveguide, which led to an improvement in the azimuthal grouping of electrons in the Larmor orbit and, as a consequence, to an increase in the lamp efficiency. A twofold increase in the waveguide length made it possible to increase the lamp gain. Ohmic energy losses in the walls of the waveguide reach 5 % of the power of the electron beam. The implementation of such a powerful gyro-TWT (2 MW) in the millimeter wavelength range will significantly increase the capabilities of radar at long distances and increase the resolution of the radar.